Influence of different formulations and process parameters during the preparation of drug-loaded PLGA microspheres evaluated by multivariate data analysis - Vysloužil Jakub; Doležel Petr; Kejdušová Martina; Mašková Eliška; Mašek Josef; Lukáč Robert; Košťál Vratislav; Vetchý David; Dvořáčková Kateřina (Acta Pharmaceutica)
The main objective of this study was to evaluate the influence of the formulation and process parameters on PLGA microparticles containing a practically insoluble model drug (ibuprofen) prepared by the o/w solvent evaporation method. Multivariate data analysis was used. The effects of altered stirring speed of a mechanical stirrer (600, 1000 rpm), emulsifier concentrations (PVA concentration 0.1 %, 1 %) and solvent selection (dichloromethane, ethyl acetate) on microparticle characteristics (encapsulation efficiency, drug loading, burst effect) were observed. It was found that with increased stirring speed, the PVA concentration or the use of ethyl acetate had a significantly negative effect on encapsulation efficiency. In addition, ethyl acetate had an adverse effect on the burst effect, while increased stirring speed had the opposite effect. Drug load was not affected by any particular variable, but rather by the interactions of evaluated variables.